Monitoring Plant Health Using a Plant Microbial Fuel Cell. (9th September 2018) - Yoon, Tae Hang; Song, Hak Jin; Jung, Woo Young; Kim, Ji Eun; Kim, Kwang Jin; Kim, Ho Hyun; Kumaran, Rangarajulu Senthil; Kim, Sunghyun; Kim, Hyung Joo
Abstract : A plant health monitoring method based on a plant microbial fuel cell (PMFC) technique was investigated. The reducing action of plant exudates on electrochemically active bacteria (EAB) in the rhizosphere was used as the basis of the method. Ardisia pusilla was used as an experimental plant. The results indicated that the open circuit potential (OCP) development from the PMFC is closely related to plant health and affected by the cultivation environment. Distinctive OCP developments were observed using the PMFC with live, dead (heat shocked), or no plant. Cultivation conditions such as watering, fertilizing, temperature variation, and lighting affected OCP development from the PMFC. Plant root viability analysis indicated that OCP development from the PMFC is closely related to plant health. These results suggest that this method based on the PMFC technique is a facile, cost‐effective, and rapid tool for monitoring plant health. Abstract :